Implementation of Virtual Reality In Residential Interior Development Case Study: Bukit Baruga - Syarief Dienan Yahya; Fizar Syafaat; Muhammad Syafaat (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The implementation of Virtual Reality (VR) in housing interior development is the focus of this research, with a case study conducted in the residential area of "Bukit Baruga." VR technology is employed to enhance user experience and improve understanding of interior design before actual implementation. This case study elaborates on the step-by-step implementation of VR in the context of housing interior development in Bukit Baruga. The research covers the design process, material selection, and virtual space arrangement, enabling prospective residents to explore and interact with the interior design before final decisions are made. The results indicate that the use of VR significantly enhances user engagement, facilitates understanding of design aspects, and provides deeper insights. However, challenges such as technological infrastructure and the need for market adaptation remain crucial considerations in VR implementation. By detailing the implementation steps and evaluating their impact, this research provides a comprehensive view of how VR technology can improve the quality of housing interior development. It is hoped that the findings of this research will serve as a foundation for further advancements in adopting VR as an effective tool in the housing development industry.